Orality and Narration. Performance and Mythic-Ritual Poetics in the Ancient World : Orality and Literacy in the Ancient World, vol. 12 - Bierl, Anton,; Bouvier, David,; Cesca, Ombretta, (Classical Studies E-Books Online, Collection 2025., 2025)
Myths can be defined as traditional stories that societies pass on from generation to generation, constantly reinventing and reshaping them through oral, written or visual representations. Rituals and cults, on the other hand, are the festive celebrations that punctuate social life, providing the occasion for the community to perform and reflect on mythic stories or mimetic plays about or by gods and heroes. How do then the recent advances in narratology, sociolinguistics, and anthropology lead us to reconsider the complex relationships between myth and ritual in ancient traditional societies, both literate and non-literate? The papers in this groundbreaking volume explore and compare these dynamic interactions across diverse cultures, including archaic and classical Greece, the ancient Near East, and imperial Rome.